PENERAPAN PENGGUNAAN MIND MAPPING BERBASIS CANVA SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PADA IPAS KELAS IV MATERI INDONESIAKU KAYA BUDAYA DI SD NEGERI 064970 - Nur Andayani, Lam; Beta Rapita Silalahi; Dinda Yarshal; Nurmairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve student learning outcomes using mind mapping in grade IV students of SD Negeri 064970 in the 2024/2025 Academic Year. This type of research is Classroom Action Research (CAR), The design of this study uses the Kemmis and Mc. Taggart model. This research was conducted in the even semester of the 2024/2025 academic year. The subjects of this study were grade IV students of SD Negeri 064970 consisting of 25 students. Data collection techniques used observation and interviews. The results of the study showed an increase in student learning outcomes, namely in cycle I by 72.60% (good category), then in cycle II it increased to 83.80% (very good category). This means that there was an increase of 11.20%. Thus, the use of Canva-Based Mind Mapping as a Learning Media can improve learning outcomes in Grade IV Science, My Indonesia is Rich in Culture, at SD Negeri 064970.